The acceptability and feasibility of a randomised trial exploring approaches to managing impacted fetal head during emergency caesarean section: a qualitative study - Gabriella Romano; Susan Ayers; Georgina Constantinou; Eleanor J. Mitchell; Rachel Plachcinski; Natalie Wakefield; Kate F. Walker (BMC Pregnancy and Childbirth, 2023)
Abstract Background Caesarean sections (CS) account for 26% of all births in the UK, of which at least 5% are done at full dilatation, in the second stage of labour. Second stage CS may be complicated by the fetal head being deeply impacted in the maternal pelvis, requiring specialist skills to achieve a safe birth. Numerous techniques are used to manage impacted fetal head, however, there are no national clinical guidelines in the UK. Aim To explore health professionals’ and women’s views on the acceptability and feasibility of a randomised controlled trial (RCT) designed to explore approaches to managing an impacted fetal head during emergency CS. Methods Semi-structured interviews with 10 obstetricians and 16 women (6 pregnant and 10 who experienced an emergency second stage CS). Interviews were transcribed and analysed using systematic thematic analysis. Results The findings considered the time at which you obtain consent, how and when information about the RCT is presented, and barriers and facilitators to recruiting health professionals and women into the RCT. Obstetricians emphasised the importance of training in the techniques, as well as the potential conflict between the RCT protocol and current site or individual practices. Women said they would trust health professionals’ to use the most appropriate technique and abandon the RCT protocol if necessary. Similarly, obstetricians raised the tension between the RCT protocol versus safety in reverting to what they knew under emergency situations. Both groups reflected on how this might affect the authenticity of the results. A range of important maternal, infant and clinical outcomes were raised by women and obstetricians. However, there were varying views on which of the two RCT designs presented to participants would be preferred. Most participants thought the RCT would be feasible and acceptable. Conclusions This study suggests an RCT designed to evaluate different techniques for managing an impacted fetal head would be feasible and acceptable. However, it also identified a number of challenges that need to be considered when designing such an RCT. Results can be used to inform the design of RCTs in this area.